1999
DOI: 10.1074/jbc.274.43.31108
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bad Phosphorylation and Association with Bcl-xL by the MAPK/Erk Kinase

Abstract: Phosphorylation of the Bcl-2 family protein Bad may represent an important bridge between survival signaling by growth factor receptors and the prevention of apoptosis. Bad phosphorylation was examined following cytokine stimulation, which revealed phosphorylation on a critical residue, serine 112, in a MEK-dependent manner. Furthermore, Bad phosphorylation also increased on several sites distinct from serine 112 but could not be detected on serine 136, previously thought to be a protein kinase B/Akt-targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
297
1
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(318 citation statements)
references
References 52 publications
15
297
1
3
Order By: Relevance
“…Both Akt and ERK can phosphorylate BAD (41,42). We observed SAA-induced phosphorylation of BAD at Ser 112 and Ser 136 consistent with activation of ERK and Akt, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…Both Akt and ERK can phosphorylate BAD (41,42). We observed SAA-induced phosphorylation of BAD at Ser 112 and Ser 136 consistent with activation of ERK and Akt, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…For example, Akt and ERKs phosphorylate Bad on distinct serines blocking its proapoptotic effects. 31,32 They also phosphorylate and inhibit caspase-9 promoting cell survival. 33,34 To conclude about the protective effect of MITC towards thymocytes, we suggested that MITC activated in thymocytes, a 'prosurvival' or 'antiapoptotic' signaling pathway involving especially ERK1/2 but also Akt which is acting upstream of ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…Not only the expression of Bcl-xL but also the membrane association of proapoptotic Bax is maintained by IL-3, and both are required for cell survival [24]. IL-3 also maintains the hyperphosphorylation of pro-apoptotic Bad both at serine 112 via the MAPK-ERK cascade and at serine 136 via the PI3K-Akt pathway, preventing its binding to BclxL [25,26]. Withdrawal of IL-3, in turn, results in the loss of all these anti-apoptotic signals.…”
Section: Discussionmentioning
confidence: 99%
“…Not only the expression of Bcl-xL but also the membrane association of pro-apoptotic Bax is maintained by IL-3, and both are required for cell survival [24]. IL-3 also maintains hyperphosphorylation of the proapoptotic Bad both at serine 112 via the MAPK-ERK cascade and at serine 136 via the PI3K-Akt pathway, preventing its binding to Bcl-xL [25,26]. Expression of another anti-apoptotic molecule, Bcl-2, is also regulated by IL-3 though the signaling mechanisms are unknown, and the anti-apoptotic potential of Bcl-2 is enhanced by phosphorylation at serine 77 by the MAPK-ERK signaling pathway [27].…”
Section: Introductionmentioning
confidence: 99%